Analysis of wood products from an added value perspective: The uruguayan forestry case - Dieste, Andrés; Noel Cabrera, María; Clavijo, Leonardo; Cassella, Norberto (Maderas. Ciencia y Tecnología, 2019)
Uruguay has a forest resource of 1 million ha plantation of fast-growing eucalyptus and pine. Short-fiber pulp is the country second export product in value, but there is also a significant production of plywood and graded kiln-dried timber from both species, used mainly for appearance applications. However, the value chain of the wood industry is not yet fully developed, particularly for pine. This study classified different existing and potential wood products using added value as criteria, calculated at the industry level by adopting a system of inputs and outputs. Hypothetical plants to manufacture these products were technical and economically analyzed: thermally modified timber, cross laminated timber, laminated veneer lumber, pine timber, bleached Eucalyptus kraft pulp, pine bleached chemical thermo-mechanical, medium density fiberboards, oriented strand board and a power plant fueled with forest biomass. The data used for this study was obtained from the final project of undergraduate engineer students of the Faculty of Engineering, Universidad de la República, Uruguay, except for the eucalyptus pulp mill, which was proposed by the authors. The results showed that wood products obtained from logs that are the main objective of the plantation presented a higher added value than those manufactured from forest residues, thinnings or chips from the sawmilling industry. Solid wood products for appearance or structural applications are at the top of added value list, considering value added per product, unit of biomass or unit of forest land per year. The integration of the value chain of the products analyzed, linking solid wood products with panels or pulp, has the potential to boost the addition of value of the forest biomass in Uruguay.